METODOLOGIAS ATIVAS E TDIC NAS PRÁTICAS PEDAGÓGICAS: UM OLHAR SOBRE A FORMAÇÃO E O TRABALHO DOCENTE NO CURSO SUPERIOR DE TECNOLOGIA EM HOTELARIA - GOMES, LUANDA FRATCHESCA (2019)
This study was carried out with the support of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES). It presents reflections on pedagogical practices of the teachers of the superior course of Hotel Technology, from a private higher education institution, in the city of São Paulo. It seeks to answer the following question: how can the use of active methodologies, in the context of the upper-level classroom of hotel technology, provide a (re) organization of teachers' practices in a meaningful and active teaching-learning perspective of the era technological? Reflecting on the role of the educator in the digital age, we investigate the use of technologies and teacher creativity, considering the use of active methodologies in the classroom based on educational experiences. A continuing training course on the use of Active Methodologies and TDIC was organized for the research participants, so that they could learn about other possibilities of working with different methodologies and technology in the classroom. The research methodology used is of a qualitative nature, in the formative perspective in narrative mode, focusing on the observation of the narrated experiences, in order to visualize a new itinerary for higher education and for meaningful learning. The professional and academic experiences of the teachers were considered, which allows the elaboration of differentiated practices, according to the context of the higher education classroom in Hospitality. The results highlight the importance of continuing education to encourage teachers to adopt new practices in the classroom, making them aware of their role, promoting active learning methodologies and the use of technologies in the connected society in which we live.